PERLINDUNGAN PADA PESERTA DIDIK DARI TINDAK KEKERASAN DI SMA NEGERI 2 TRENGGALEK - Dining Hanifah Citra Kumala; Listyaningsih Listyaningsih (Universitas Negeri Surabaya (Unesa), 2022)
This study aims to determine the forms of violence against students and to determine the impact and protections provided by schools in dealing with cases of violence. The metod used in this research is a qualitative method with a case study design. Collecting data in this study by means of observation and semi structured interviews, as well as informants in this study, namely Counseling Guidance teachers, Child Friendly School team teachers, and also victims of cases of violence. The data analysis technique in this study is data collection, data editor, and data presentation. The results of this study indicate that the form of violence that occurs in schools is physical violence that causes injuries to students who are victims of violence. As for the protection provided by schools against cases of violence that occur, the school coordinates with related agencies, namely the Social Service and the Health Office so that the handling of cases correct. The protection provided by high school 2 Trenggalek is very good, this is evidenced by the completion of this case of violence properly and not detrimental to either party, and of course the school in providing protection is also in accordance with the Law on Child Protection Number 35 of 2014. Even now high school 2 Trenggalek is one of the best examples of school in Trenggalek.It is the duty of every school providing protection to their students so that they are comfortable and safe in the school environment.